2021
DOI: 10.1108/meq-05-2021-0109
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the validity of the agricultural-induced environmental Kuznets curve (EKC) hypothesis for Ghana: evidence from an autoregressive distributed lag (ARDL) approach with a structural break

Abstract: PurposeThe purpose of this research is to examine the validity of the agriculture-induced environmental Kuznets curve (EKC) hypothesis with evidence from an autoregressive distributed lag (ARDL) approach with a structural break including real income and energy consumption in the model for Ghana over the period 1980–2014.Design/methodology/approachThe ARDL approach with a structural break was used to analyze the agriculture-induced EKC model which has not been studied in Ghana. The dynamic ordinary least square… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 118 publications
0
5
0
Order By: Relevance
“…Stationarity test shows the level of integration of each variable understudy. Similar work has been conducted by some scholars [39][40][41] using ARDL model.…”
Section: Model Estimation Proceduresmentioning
confidence: 57%
See 1 more Smart Citation
“…Stationarity test shows the level of integration of each variable understudy. Similar work has been conducted by some scholars [39][40][41] using ARDL model.…”
Section: Model Estimation Proceduresmentioning
confidence: 57%
“…The first step in the ARDL relationship analysis is the stationarity test (unit root test) [39]. Stationarity test shows the level of integration of each variable understudy.…”
Section: Model Estimation Proceduresmentioning
confidence: 99%
“…To this day, numerous studies confirmed the presence of the EKC model in various types of environmental degradation indicators; for instance, EKC-carbon dioxide (Prastiyo et al, 2020;Danish et al, 2021;Koshta et al, 2021;Ntim-Amo et al, 2022;Massagony and Budiono, 2023), EKC-ecological footprint (Ulucak and Bilgili, 2018;Ansari, 2022;Fatima et al, 2021;Ozturk et al, 2023); EKCdeforestation (Waluyo and Terawaki, 2016;Ajanaku and Collins, 2021;Destiartono and Ekananda, 2023Caravaggio, 2020and Tsiantikoudis et al, 2019; and EKC-nitrous oxide (Islam, 2021 andCho et al, 2014). In accordance with methane emissions, the Kuznets' turning point can be smoothed by advancing the role of renewable energy, crop diversification, and technological innovation (Islam, 2021).…”
Section: Literature Reviewmentioning
confidence: 92%
“…Industrialization has been found to increase carbon dioxide emissions by Aboagye (2017). While Ntim-Amo et al (2021) reported that agriculture increases carbon dioxide emissions in their studies; Prastiyo and Hardyastuti (2020) had contrary results.…”
Section: Literature Reviewmentioning
confidence: 93%